Histiocytic Sarcoma in a Kidney Transplant Patient: A Case Report and Review of the Literature. (3rd October 2016) - Pollen, Maressa; El Jamal, Siraj; Lewin, Jack; Manucha, Varsha
Abstract : Objective . Histiocytic sarcoma (HS) is an aggressive neoplasm with only limited number of reported series of cases and rare case reports of occurrence as a posttransplant neoplastic disorder. The etiology and pathogenesis of the disease is unknown and the optimal treatment is still under investigation. We describe an unusual case of HS in a patient with a remote history of kidney transplant. Method and Results . A 54-year-old male with a remote history of renal transplantation under maintenance immunosuppression presented with features of sepsis. CT abdomen revealed multiple heterogeneous masses in bilateral native kidneys and liver and enlarged abdominal and retroperitoneal lymph nodes. Viral serology work-up was negative. Needle core biopsy revealed a highly undifferentiated neoplasm comprised of highly atypical large cells with eosinophilic to vacuolated cytoplasm and hemophagocytosis. Extended panel of immunohistochemistry proved histiocytic lineage for the tumor cells. The patient expired 2 weeks following the diagnosis. Conclusion . Our case along with three previously published case reports raised the possibility of HS as a treatment-related neoplasm or a posttransplantation neoplastic disorder in solid organ transplant recipients.